OPTIMALISASI SUMBER DAYA MANUSIA MELALUI PERANAN KNOWLEDGE SHARING DI ORGANISASI PEMBINAAN ANAK-ANAK SALMAN INSTITUT TEKNOLOGI BANDUNG (PAS ITB) - Fadhilah Hartary Barkah; Rusmana, Agus; Khairul Anwar, Rully (Program Studi Perpustakaan dan Ilmu Informasi, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2024)
As a coaching or teaching organization for children, members of the organization or what are usually called PAS ITB supervisors implement knowledge sharing activities to eliminate knowledge gaps between supervisors who have various characters and different educational backgrounds. Knowledge sharing helps in increasing the competence of each individual so that optimization of human resources in the organization can be created and organizational performance can increase. The aim of this research is to find out the role of knowledge sharing in the PAS ITB organization and what the supporting and inhibiting factors are for knowledge sharing in the PAS ITB organization. The method used in this research is a qualitative method with a case study approach. Based on the research results, it can be concluded that the implementation of knowledge sharing at PAS ITB includes various activities, namely work meetings, mentoring of seniors, consolidation, morning dew, evaluation, large socialization and casual discussions between PAS ITB seniors. Knowledge management is carried out in the form of sorting various information or documentation of activities via centralized links, classifying documents via Google Drive and disseminating content or information via social media. Supporting factors for knowledge sharing at PAS ITB are trust and openness, organizational culture, reciprocal relationships between senders and recipients of knowledge and support from leaders. Meanwhile, the factors inhibiting knowledge sharing at PAS ITB are lack of full involvement of organizational members, lack of maximum documentation and lack of use of ICT (Information and Communication Technology).